(untitled) (The International Journal for Scientific Research, 2026)
The aim of this study was to identify the effect of using the Knowledge of Performance (KP) and Knowledge of Result (KR) methods on learning offensive basketball skills among students. It also sought to compare the post-test result between the first experimental group, which used the Knowledge of Performance method, and the second experimental group, which used the Knowledge of Result method in learning offensive basketball skills. The researchers hypothesized that there would be statistically significant differences between the pre-test and post-test result for both the first experimental group that used the Knowledge of Performance (KP) method and the second experimental group that used the Knowledge of Result (KR) method in learning offensive basketball skills. The researchers also hypothesized that there would be significant differences in the post-test results between the two experimental groups in the level of skill performance of offensive basketball skills. The experimental method was adopted due to its suitability for the nature of the study. The research population was intentionally selected from second-grade intermediate school students at Al-Taghlub Intermediate School for Boys in Qaraqosh during the 2025–2026 academic year. The population consisted of 32 students distributed into two experimental groups. The research sample was selected using a purposive-random approach. Equivalence between the two groups was established in terms of physical fitness components, perceptual-motor abilities, and offensive basketball skills. The researchers used personal interviews, questionnaires, and tests as research tools for data collection. The following statistical methods were employed: mean, standard deviation, skewness coefficient, coefficient of variation, independent-samples t-test, and paired-samples t-test. The findings indicated that both educational programs, accompanied by the Knowledge of Performance and Knowledge of Result methods, had a positive effect on learning some offensive basketball skills among students in the two experimental groups, highlighting their importance in the learning process. However, the first experimental group, which used the Knowledge of Performance method, outperformed the second experimental group, which used the Knowledge of Results method, in learning and improving the technical performance of certain offensive basketball skills. The researchers recommended the use of both educational programs accompanied by the Knowledge of Performance and Knowledge of Result methods for teaching offensive basketball skills. They also emphasized the importance of focusing on the Knowledge of Performance method due to its positive and effective role in accelerating the learning of offensive basketball skills, particularly among students in the first experimental group.